East coast identity of Kuantan: Taman Gelora as a recreational coastal park - Md Nazir, Muhammad Amirul Hanis; Ibrahim, Putri Haryati; Md Jani, Haza Hanurhaza (IIUM Press, 2024)
This project aims to transform the Taman Gelora site in Kuantan into a coastal park in order to promote Kuantan's east coast identity. As a result, it is proposed that this project include the beach as an extension of Taman Gelora in order to create a coastal recreational park. The project is in the state of Pahang, east of Kuantan, and faces the South China Sea. The park is designated as a local park and is open to the public for recreation. The park, which covers approximately 28 hectares, was established in the 1980s. Taman Gelora is made up of a number of man-made lakes and other recreational amenities. Some of the issues identified include a disjointed shore, deteriorating water quality, and ineffective facilities. There are several entrances to the area, but the park itself is located on a slightly hidden edge of Kuantan, making it less visible to unknowing eyes. Based on these situations, the project has aimed at addressing the identified issues while also successfully promoting Taman Gelora as a recreational coastal park that can be the pride of Kuantan as an important east coast city.